A comparison of 4-year entecavir efficacy in nucleos(t)ide analog-naïve and -experienced adult Taiwanese chronic hepatitis B patients - Chen, Chien-Hung; Hu, Tsung-Hui; Hung, Chao-Hung; Lu, Sheng-Nan; Wang, Jing-Houng; Chang, Min-Hui; Changchien, Chi-Sin; Lee, Chuan-Mo (Hepatology international, 2013)
Purpose To compare the efficacy of entecavir (ETV) monotherapy up to 4 years in nucleos(t)ide analog (NA)-experienced and -naïve subjects. Methods One hundred sixty NA-experienced and 282 naïve chronic hepatitis B patients who were treated with ETV were enrolled. Of the 160 NA-experienced patients, 49 had prior lamivudine (LAM)-resistant mutants, 18 had resistant mutants to LAM followed by adefovir (ADV) after switching to ADV sequential therapy (LAM/ADV resistance), and 9 had prior ADV-resistant mutants. NA-resistant mutants were detected by line probe assay. Results Four years of ETV therapy resulted in virological response (VR, HBV DNA < 300 copies/ml), HBeAg seroconversion, and ETV-resistant mutants development in 98.2, 45.2, and <1 % of naïve patients, respectively. LAM- and ADV-experienced patients who never developed LAM-resistant mutants had similar VR and ETV-resistant mutant rates to NA-naïve patients. In contrast, prior LAM-resistant mutants were significantly associated with higher ETV-resistant mutants development and reduced VR rates. Patients with prior LAM-resistant mutants but not at baseline had a lower rate of ETV-resistant mutants compared to those with baseline LAM-resistant mutants [hazard ratio (HR): 0.58, 95 % confidence interval (CI): 0.35–0.95] and those who had LAM/ADV resistance (HR:0.16, 95 % CI:1.0.03–0.76). Early add-on ADV achieved VR in eight of nine patients with ETV-resistant mutants when HBV DNA was <2 × 10 5 copies/ml. Conclusions Entecavir was highly efficacious and low resistance in NA-naïve, LAM-, or ADV-experienced patients without LAM-resistant mutants. Patients with prior LAM-resistant mutants but not at baseline had lower ETV-resistant mutant rates compared to those with baseline LAM-resistant mutants or LAM/ADV resistance.